Prevotella genus and its related NOD-like receptor signaling pathway in young males with stage III periodontitis - Zhao, Yaqiong; Ye, Qin; Feng, Yao; Chen, Yun; Tan, Li; Ouyang, Zeyue; Zhao, Jie; Hu, Jing; Chen, Ningxin; Su, Xiaolin; Dusenge, Marie Aimee; Feng, Yunzhi; et al. (Frontiers in Microbiology, 2022)
Background: As periodontitis progresses, the oral microbiota community changes dynamically. In this study, we evaluated the dominant bacteria and their roles in the potential pathway in young males with stage Ⅲ periodontitis. Methods: 16S rRNA sequencing was performed to evaluate variations in the composition of oral bacteria between males with stage Ⅰ and Ⅲ periodontitis and identify the dominant bacteria of each group. Function prediction was obtained based on 16S rRNA sequencing data. The inhibitor of the predominant pathway for stage III periodontitis was used to investigate the role of the dominant bacteria in periodontitis in vivo and in vitro. Results: Chao1 index, Observed Species and Phylogenetic Diversity (PD) whole tree values were significantly higher in the stage Ⅲ periodontitis group. β diversity suggested that samples could be divided according to the stages of periodontitis. The dominant bacteria in stage Ⅲ periodontitis were Prevotella, Prevotella_7, and Dialister, whereas that in stage Ⅰ periodontitis was Cardiobacterium. KEGG analysis predicted that variations in the oral microbiome may be related to the NOD-like receptor signaling pathway. The inhibitor of this pathway, NOD-IN-1, decreased P. intermedia -induced Tnf-α mRNA expression and increased P. intermedia -induced Il-6 mRNA expression, consistent with the ELISA results. Immunohistochemistry confirmed the down-regulation of TNF-α and IL-6 expressions by NOD-IN-1 in P. intermedia–induced periodontitis. Conclusion: The composition of the oral bacteria in young males varied according to the stage of periodontitis. The species richness of oral microtia was greater in young males with stage Ⅲ periodontitis than those with stage Ⅰ periodontitis. Prevotella was the dominant bacteria in young males with stage Ⅲ periodontitis, and inhibition of the NOD-like receptor signaling pathway can decrease the periodontal inflammation induced by P. intermedia.